Memories of Asaph : Mnemohistory and the Psalms of Asaph - Jacobson, Karl N., 1969- (Book collections on Project MUSE., 2017)
"Although the Psalms of Asaph (Psalms. 50, 73-83) contain a concentration of historical referents unparalleled in the Psalter, they have rarely attracted sustained historical interest. Karl N. Jacobson identifies these Psalms as containing cultic historiography, historical narratives written for recitation in worship, and explores them through mnemohistory, attending to how the past is remembered and to the rhetorical function of recitation in the cultic setting. Asaph "remembers" the past as a movement from henotheism to Yahwism as the core memory that informs a new historical situation for worship participants"--Page 4 of cover.